Hutan Mangrove sebagai Laboratorium Alam (Studi Kasus Pembelajaran Ekosistem dan Penguatan Kesadaran Lingkungan melalui Kuliah Lapangan Mahasiswa PGSD di Desa Wisata Manyampa, Kabupaten Bulukumba) - Sahabuddin, Erma Suryani (Universtas Negeri Makassar, 2025)
This study aims to examine in depth the experience of Elementary School Teacher Education (PGSD) students in field lecture activities in the mangrove forest ecosystem of Mamampa Tourism Village, Ujungloe District, Bulukumba Regency. This activity is part of the Environmental Education (PLH) course and integrates ecosystem learning and community service. The research uses a qualitative approach with a case study method. Data was collected through field observations, student reflective journals, documentation, and in-depth interviews with students, lecturers, and various local stakeholders (village heads, tourist visitors, managers, tourism agencies, and NGOs). The results of the study show that hands-on experience in the field forms a more contextual understanding of the concept of ecosystems and increases students' environmental awareness, especially in terms of waste management and mangrove conservation. This study recommends a wider integration of nature-based learning in the PGSD curriculum.